Microlessons in Chinese Universities: Concepts, Technology, and Case Analyses - Zhao, Guodong; Wang, Bingyi; Liu, Jinglu; Wang, Jingxing (Blended Learning: Aligning Theory with Practices, 2016)
The objective of this paper is analyze 1,500 microlessons in regard to design, technical features, types, and development problems. The microlessons had all been entered in China’s National Multimedia Courseware. Relevant suggestions and strategies are also offered on the use of microlessons in higher education. The relationships among the five key concepts, namely, microlesson, Flipped Classroom, SPOC, MOOCs and Rapid E-learning, are described. This paper then proposed a Five-in-one Relation Model and Four Stage Model of Microlesson Evolution. Microlessons are categorized, based on their technical complexity, captioning, language fluency, video clarity, teaching skill, overall video effects and comprehensiveness. Instructional design, technical realization, and presentation effect are considered. In this paper, two microlesson cases are analyzed. The problems related to microlesson development are summarized, and proposals are made for improvement measures.